ANALISIS KINERJA SEKOLAH (STUDI KASUS SDN 002 KOTO PERAKU KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI) - Trini May Dilla; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Elementary school 002 Koto Peraku is unit technical institution from Kuansing department. The function is giving attendant to make students intelligence in area subdistrict Cerenti. To create the purpose of education can useful for people or public, performance of school is influences to know the capability education in this school. But, these performance of school at SDN 002 Koto Peraku subdistrict Cerenti, Kuansing regency still low.Researcher use teori based on Mohamad Mahsun said there is some indicator in performance of organization: input, process, and output. The purpose of this research is to analyze how performance of school at SDN 002 Koto Peraku subdistrict Cerenti, Kuantan Singingi regency. This research is descriptive research the researcher. Used metode avalitative and snowball sampling to get the data the researcher use interview, observation, and documentation.Result of this result is performance of school at the SDN 002 Koto Peraku still low because lers the teacher (need teacher) means need teacher based on quality and quantity at this school sarana and prasarana still low to increase process studying. Support factor performance of school is teamwork all the teacher, obstacle factor performance of school is headmaster at school dont care with teacher and students, individual factor the teacher cant develop individual, system factor facilities of school dont enought to increase students and situational factor area at the school dont comfortable and safe for students.Keyward : Analyze, Performance